Dirigent proteins in plants: modulating cell wall metabolism during abiotic and biotic stress exposure - Paniagua, Candelas; Bilkova, Anna; Jackson, Phil; Dabravolski, Siarhei; Riber, Willi; Didi, Vojtech; Houser, Josef; Gigli-Bisceglia, Nora; Wimmerova, Michaela; Budínská, Eva; Hamann, Thorsten; Hejatko, Jan (Oxford University Press, 2017)
Dirigent (DIR) proteins were found to mediate regio- and stereoselectivity of bimolecular phenoxy radical coupling during lignan biosynthesis. Here we summarize the current knowledge of the importance of DIR proteins in lignan and lignin biosynthesis and highlight their possible importance in plant development. We focus on the still rather enigmatic Arabidopsis DIR gene family, discussing the few members with known functional importance. We comment on recent discoveries describing the detailed structure of two DIR proteins with implications in the mechanism of DIR-mediated catalysis. Further, we summarize the ample evidence for stress-induced dirigent gene expression, suggesting the role of DIRs in adaptive responses. In the second part of our work, we present a preliminary bioinformatics-based charac- terization of the AtDIR family. The phylogenetic analysis of AtDIRs complemented by comparison with DIR proteins of mostly known function from other species allowed us to suggest possible roles for several members of this family and identify interesting AtDIR targets for further study. Finally, based on the available metadata and our in silico analysis of AtDIR promoters, we hypothesize about the existence of specific transcriptional controls for individual AtDIR genes and implicate them in various stress responses, hormonal regulations, and developmental processes.
Este artículo revisa el papel de las proteínas Dirigent (DIR) en la biosíntesis de lignanos y lignina, y su posible importancia en el desarrollo de las plantas. Destaca estudios sobre la familia de genes DIR en *Arabidopsis*, que aún es poco comprendida, y analiza la estructura de algunas proteínas DIR con implicaciones en su mecanismo catalítico. También se discute la evidencia que relaciona la expresión de genes DIR con respuestas al estrés, sugiriendo que estas proteínas pueden tener un papel en la adaptación de las plantas. Además, se presenta un análisis filogenético de los genes *AtDIR*, proponiendo funciones potenciales para varios miembros y su posible control transcripcional en respuestas al estrés y procesos de desarrollo.
Keywords: Paredes celulares vegetales; Plantas; Biosíntesis; Biotic and abiotic stress response; cell walls; dirigent protein; lignan; lignin; regioselectivity; stereoselectivity